Micropropagation, pigments extraction and antimicrobial activity of Cucumis melo L. / Siti Aisha Na’illa Che Musa - Siti Aisha Na’illa , Che Musa (2017)
In vitro regeneration of Cucumis melo L. was successfully achieved in this study. The best seeds germination polarity was horizontal position cultured on MS medium without plant growth regulators. Explants from 7-day-old aseptic seedlings were used as explant sources for subsequent experiments since the explants gave the best response at this age. Different responses were observed when cotyledonary petioles were cultured on MS media supplemented with different concentrations of 2,4-D and coconut water for in vitro regeneration study. Results obtained showed the best media was MS supplemented with 1 mg/L 2,4-D with the combination of 25% of coconut water which gave 100% shoots and 66.67% roots. For callus induction, 4 types of explants were tested includes hypocotyl, cotyledon, node, and leaf cultured on MS media supplemented with different concentrations of BAP and 2,4-D. All of the explants induced callus except leaf explants. The highest rate of callus formation was observed from hypocotyl explants, followed by node explants, and the least callus proliferation was observed on cotyledon explant. Node and hypocotyl explants were then used in induction of embryogenic callus. The highest embryogenic callus obtained from node explants cultured on MS media supplemented with 2 mg/L BAP in combination with 1 mg/L 2,4-D (100.00 %) with the average rate of the shoot formation of 13.10 ± 0.36 per explant. Hypocotyl explants induced non embryogenic callus on MS media supplemented with BAP and 2,4-D but on MS media supplemented with different concentrations of IAA and Kin, hypocotyls induced callus with root formation, where the highest root formation (86.67%) with the average roots formation of 4.20 ±0.50 per explant were observed on MS media supplemented with 3 mg/L IAA. However, callus induced on MS media supplemented with 0.1 M of mannitol regenerated high rate of shoots where the highest rate was observed from node explants (76.67%). Shoots obtained were transferred to MS medium without plant growth regulators for roots formation (93.33%). After 2 months, the established plantlets were then transferred to 3 types of substrates for acclimatization process where the best substrate medium was black soil, followed by mixture of black soil and red soil (1:1) and cocopeat. For carotenoids and chlorophyll pigments extraction, acetone was identified as the best extraction solvent. For colour stability, the pigments were most stable at pH 9 where the colour was last faded. In the application of pigments in coating technology, carotenoids gave the weakest response compared to chlorophyll where the color faded with increasing temperature. In antimicrobial studies, the non embryogenic callus induced from hypocotyl explant on MS media supplemented with 1 mg/L of BAP and 1 mg/L of 2,4-D (1.58 g fresh weight) and in vitro hypocotyl were harvested and extracted with methanol. The extracts were tested against Escherichia coli, Bacillus subtillis, and Staphylococcus aureus, Aspergillus niger, Penicillium sp, and Fusarium sp. The strongest antimicrobial activity of callus extract was observed against Bacillus subtilis and Penicillim sp with inhibition zone of 14 mm and 11 mm, respectively.